KEDUDUKAN WANITA DALAM PERNIKAHAN ADAT REJANG - Albuhari Albuhari (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2021)
This study aimed to know the views of Islam, culture, and gender equality on the position of women in the marriage procession of Rejang’s culture. This study was conducted in Karang Anyar, Curup, Bengkulu, using a qualitative method. This study involved several data sources, namely the Chairman of BMA Karang Anyar Village, residents of Karang Anyar, and informants. Data were collected using several techniques, namely observations, interviews, and documentation, which were further analyzed using an interactive model. The findings revealed that there are two terms used in Rejang’s customary marriage. The first term refers to bleket or beleket and the second is semendo or semendoriang. Both terms have distinctive patterns that contradict each other. The marriages of beleket and semendo do not actually deviate from Islamic teachings. It is only in the aspect of social status which lies a gap. The typical pattern of beleket marriage is that the husband has complete rights to own the wife, and any authority is in the hands of the husband. While, the special pattern of semendo is that both husband and wife have rights and obligations in carrying out the married life. The husband cannot be authoritarian in any way. Basically, the Rejang tribe itself regards women properly. Along with the change from time to time the cultures of beleket and semendo’s marriages disappear over time. For now, in general, it is difficult to find belekt or semendo marriage.